(untitled) (Bangladesh Journal of Botany, 2018)
A comprehensive study was carried out to investigate phytoplankton community and water quality in the Digboi oil refinery effluent stream. Taxonomic composition, abundance, spatial distribution, temporal dynamics of phytoplankton were studied along with physicochemical properties of water based on monthly data collected from seven selected sampling stations during April, 2011 - March, 2012. Altogether 139 species (7 orders, 19 families, 67 genera) of phytoplankton were identified of which Bacillariophyceae was the dominant class with 45 species followed by Chlorophyceae 40, Cyanophyceae 34 and Euglenophyceae 20. Though distinct changes in community structure were reported, higher phytoplankton abundance revealed during the post monsoon months. Correlation analysis showed influence of phenol and total oil content (TOC) along with pH, inorganic phosphorus and nitrate content in distribution and abundance of the phytoplankton.